Understanding differences and disorders of sex development (DSD) - Hiort, Olaf; Ahmed, S. F (Karger, 2014)
Nakladatelská anotace: Ten years ago a group of experts assembled in Chicago to develop a consensus on the management of conditions previously described as intersex. The consequences of this consensus have been far reaching, including a change in nomenclature, the development of greater collaboration across geographical boundaries, and a move towards greater involvement of patients and parents. Moreover, an international registry was established, as well as research and clinical networks. This book brings together a thorough overview on all these topics. Furthermore, the major technological advances in diagnostic genetic and biochemical capabilities over the past 10 years are outlined in detail. Offering a comprehensive update on various aspects of disorders of sex development (DSD), this book will be essential reading to all clinicians who are involved in delivering health care to patients with a DSD, as well as scientists involved in biomedical research related to DSD. -
Endocrine development, ISSN 1421-7082 vol. 27
Keywords: Sex Differentiation; Disorders of Sex Development; Endocrine System; sexuální diferenciace; poruchy sexuálního vývoje; endokrinologie; endokrinní systém